Domestic Debt Markets in Sub-Saharan Africa - Christensen, Jakob (Washington, D.C. : International Monetary Fund, 2004)
This study discusses the role of domestic debt markets in sub-Saharan Africa (SSA) based on a new dataset covering 27 SSA countries during the 20-year period 1980-2000. The study finds that domestic debt markets in these countries are generally small, highly short-term in nature, and often have a narrow investor base. Domestic interest payments present a significant burden to the budget, despite much smaller domestic than foreign indebtedness. The use of domestic debt is also found to have significantly crowded out private sector lending. Finally, the study identifies significant differences between the size, cost, and maturity structure of domestic debt markets in HIPCs and non-HIPCs.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet